1. Zredukuj wyraz podobne.
a . -4x - 7 -3x + 7 = ?
b . x - 2xy + ½x - ⅓xy = ?
c . -x² + y² - 2x² - 2y² = ?
d . -x² + 2x - 3x + x² = ?
e . 4x + 4 - 7x - ½ = ?
f . -2ab + 12a - 4ab - 16a = ?


2. Zapisz w jak najprostszej postaci.
a . (a+b) - (2a - b) - (a - 2b) = ?
b . (3x - y + 1) - (x + y) + (y - x) = ?
c . -(kx + ny) - (3kx + 2ny) + (5kx - 3ny) = ?
d. (2ab + a + 3) - (3ab - a + 3) = ?
e . (4x² - 3x) - (x + 0,1x²) - (x² - 0,1x) = ?

2

Odpowiedzi

2010-03-03T22:47:33+01:00
A . -4x - 7 -3x + 7 = -7x
b . x - 2xy + x½ - ⅓xy = 1½x - 2⅓xy
c . -x² + y² - 2x² - 2y² = -3x² - y²
d . -x² + 2x - 3x + x² = -x
e . 4x + 4 - 7x - ½ = -3x + 3½
f . -2ab + 12a - 4ab - 16a = - 6ab - 4a
2010-03-03T22:55:27+01:00
1. a) -4x - 7 -3x +7= -7x
b)x - 2xy + ½x - ⅓xy = 1,5x- 2 1/3
c . -x² + y² - 2x² - 2y² = -3x²y²
d . -x² + 2x - 3x + x² = -x
e . 4x + 4 - 7x - ½ = -3 + 3,5
f . -2ab + 12a - 4ab - 16a = -6ab - 4a

2.
a . (a+b) - (2a - b) - (a - 2b) = a+b-2a+b-a+2b=-2a+4b
b . (3x - y + 1) - (x + y) + (y - x) = 3x-y+1-x-y+x-y=3x-3y+1
c . -(kx + ny) - (3kx + 2ny) + (5kx - 3ny) = -kx-ny-3kx-2ny+5kx-3ny= -1kx-6ny
d. (2ab + a + 3) - (3ab - a + 3) = 2ab+a+3-3ab+a-3= -ab+2a
e . (4x² - 3x) - (x + 0,1x²) - (x² - 0,1x) = 4x²-3x-x-0,1x²-x²+0,1x= 2,9x²-3,9x